Effects of nutrition on degree of anaemia and liveweight changes in N'Dama cattle infected with trypanosomes - Agyemang, K.; Dwinger, R.H.; Touray, B.N.; Jeannin, P.; Fofana, D.; Grieve, A.S. (Elsevier, 1990)
Six herds of N'Dama cattle exposed to low to medium tsetse challenge in areas surrounding the village of Keneba in the Kiang West District of The Gambia, were monitored. The degree of anaemia, as measured by PCV in 2- to 5-year-old female N'Dama cattle during the first month of detectable trypanosome infection, and the pattern of recovery from anaemia during the first 3 and 6 months pi were compared for 4 groups of cattle, of which 2 groups served as controls. Group 1 consisted of 13 cattle kept under village management conditions which became infected with Trypanosoma congolense while grazing in woodlands and natural unimproved pastures. The 13 cattle of Group 2 were managed similarly to Group 1 but were not infected and constituted the first control grouGroups 3 and 4, with 14 cattle each, were kept in the same village but received, in addition to grazing, 4 kg/head/day of a mixture of rice bran, groundnut cake, milled Andropogon hay and common salt. Cattle in Group 3 became infected with the same species of trypanosome as Group 1. Cattle in Group 4 were not infected and served as the 2nd control grouResults from these comparisons showed that during the first 4 weeks after infection, cattle in Group 3 developed anaemia to the same degree as those in Group 1, but recovered from the anaemia more rapidly. It is concluded that plane of nutrition in N'Dama plays an important role in the rate of recovery from anaemia produced by trypanosome infections and the lack of adequate nutrition that occurs under field conditions would constitute a stressful condition that could weaken the degree of trypanotolerance of the animals.